Maternal and fetal toxicity of Wistar rats exposed to herbicide metolachlor - Kátia Cristina de Melo Tavares Vieira; Jennifer Cardoso Couto; Edson Zanetti; José Marcos Sanches Junior; Ana Paula Alves Favareto (Acta Scientiarum. Biological Sciences, 2016)
Metolachlor is a selective pre-emergent herbicide widely used in agriculture to control weeds. The aim of this study was to evaluate the possible effects of metolachlor on reproductive performance of adult rats, as well as its teratogenic potential when administered during the period of organogenesis. Pregnant adult female rats were allocated into 4 experimental groups (n = 10 group-1), that received 0 (control); 150 (TA); 300 (TB); or 1000 mg kg-1 bw day-1 (TC) of metolachlor, by gavage, from the 6th to 15th gestational day (GD). There is reduction in the weight gain of the animals from TB and TC groups compared to the control group. Liver and placenta weights were reduced in TB and TC groups, respectively, while the percentage of post-implantation loss was increased in the TC group. There were no external malformations in either rat of the control or treated groups. However, an increased incidence of skeletal anomalies and visceral anomalies (especially in the urogenital system) was observed in TC group. These results demonstrate that exposure of pregnant rats to metolachlor can lead to signs of general toxicity, late embryonic losses and congenital anomalies.